Merger Of Telekom Malaysia Berhad And Technology Resource Industry Berhad - Sen, Tan Chen (2002)
Having acquired two smaller cellular competitors, TMB did not manage to challenge TRI or Maxis Mobile Communication in the Cellular market. Seeing TRI in financial difficulty and an opportunity to become the leading mobile operators in Malaysia, TMB initiated an effort to take control of TRI. Started with friendly negotiation which quickly became a hostile battle, TMB eventually managed to gain a controlling stake in TRI as well as won the battle for control of the boardroom, however, TMB did not manage to gain the confident of the minority share holders in TRI, hindering its intention to merge its revenue loosing cellular subsidiary with TRI's mobile subsidiary Celcom. At the point of this report being written, events between TMB and TRI continue. My report of the merger exercise focus on all events in the period between December 2001 and July 2002. As of August 2002, TMB has not succeeded to merge TMTouch with TRI.